APPLICATION OF GEOELECTRICAL METHODS FOR IDENTIFICATION OF SOIL LAYER - Latif, Devi Oktaviana; Hazhiyah, Amalia Ula; Purnama, Adhitya Yoga (Journal of Applied Engineering Science, 2021)
Landslide is a geological event caused by the movement of rock or land mass that can be defined as the displacement of slope-forming material, which is the original rock as well as the other material that is moving with the gravity. The factors that influence landslides are soil layer, slip surface and saturated soil. Mapping or determining the landslide area is done by identifying several parameters that can trigger landslide. The geophysical method that can be used to analyse soil layer is resistance type of geoelectrical. Variations of each rock or soil layer resistance below the measuring point can be obtained from the measurements of current and potential differences. The research site is located East Aceh district, Indonesia. Geoelectrical measurements using Wenner-Schlumberger electrode configuration. Based on geological information, field observation and geophysical measuring results, the area is dominated by clay, sand and gravel material. Lithology of clay dominates the underside of the surface (until the depth of ± 30 meters. water that is held in sand lithology causes saturation of the sand. this is because there is a layer of clay under the sand which has low permeability or even impermeable properties. Saturated sand lithology can lead to contact between particles and has the potential to weaken it, causing soil movement.